2014
DOI: 10.1039/c4dt01047g
|View full text |Cite
|
Sign up to set email alerts
|

Pincer versus pseudopincer: isomerism in palladium(ii) complexes bearing κ3C,S,C ligands

Abstract: In NHC pincer complexes incorporating a hemilabile donor site, there exists an equilibrium between the true pincer form and a pseudopincer coordination isomer. The influence of the NHC moieties on this isomerism has been studied by DFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
(9 reference statements)
2
2
0
Order By: Relevance
“…As previously observed, the coordination modes of diNHC ligands can also be controlled by the electron-donating ability of the NHC units. Therefore, the benzimidazolinylidene donors of ligands A and B were substituted by more weakly donating 1,2,4-triazolinylidene units while the design was kept otherwise unchanged. The triazolium salts (H 2 C )­Br 2 and (H 2 D )­Br 2 were prepared as reported and reacted with Pd­(OAc) 2 under the same conditions (Scheme ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As previously observed, the coordination modes of diNHC ligands can also be controlled by the electron-donating ability of the NHC units. Therefore, the benzimidazolinylidene donors of ligands A and B were substituted by more weakly donating 1,2,4-triazolinylidene units while the design was kept otherwise unchanged. The triazolium salts (H 2 C )­Br 2 and (H 2 D )­Br 2 were prepared as reported and reacted with Pd­(OAc) 2 under the same conditions (Scheme ).…”
Section: Resultssupporting
confidence: 90%
“…Here, the introduction of flexible linkers can lead to interesting outcomes that can enhance our understanding of NHC chemistry. For example, we have observed that CSC pincer-type diNHC ligands can coordinate to palladium in either a tridentate or a bidentate fashion, which can be controlled by the donor ability of the NHC units. In an extension of this concept, one could hypothesize that the coordination mode of a potentially tetradentate diNHC ligand could be controlled in a similar fashion. Herein, we disclose the preparation and structural characterization of several new palladium­(II) complexes, in which the binding of potentially tetradentate ligands can be easily controlled by design and electronic factors.…”
Section: Introductionsupporting
confidence: 76%
“…Their weak donor capability makes them suitable candidates for the design of hemilabile hybrid ligands for catalysis. For example, complexes of thioether‐functionalized NHC ligands have shown promising catalytic activities and an interesting structural dynamics . However, less attention has been paid to the measurement of their electron donating abilities compared to those of the other ligands.…”
Section: Resultsmentioning
confidence: 99%
“…For example, complexes of thioether-functionalized NHC ligandsh ave shown promising catalytic activities and an interesting structural dynamics. [30][31][32][33][34] However,l ess attention has been paid to the measurement of their electron donating abilities compared to those of the other ligands. Herein, the electron donating ability of two common thioethers, that is, dimethylsulfide (DMS)a nd tetrahydrothiophene (THT) are assessed.…”
Section: Determining the Heps Of Selected Neutralchalcogen Donorsmentioning
confidence: 99%